2016
DOI: 10.5455/ijmsph.2016.11102015203
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of refractive error among school-going children of Imphal, Manipur

Abstract: Background: Uncorrected refractive error is the leading cause of eye problem and the second cause of blindness worldwide. Among children aged 5-15 years, 12.8 million are visually impaired because of refractive errors. Objective: To assess the magnitude of refractive error among school-going children of Imphal, Manipur, India, and to determine the association between refractive error and variables such as sex, dietary habits, family history, and daily activities such as watching television and using computers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
(12 reference statements)
2
7
0
Order By: Relevance
“…The prevalence of 30.74% refractive error seen in this study is similar to the result of a study conducted in Western Saudi Arabia among 3-10 years old children which reported a prevalence of 34.9% of uncorrected refractive error among this population (2). Also, this prevalence is comparable to what was reported in Imphal, Manipur India, where the prevalence of 29.14% refractive error among school children was also reported (8). These similarities may be explained by the fact that both studies adopted a similar working de nition for refractive error, that is:…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of 30.74% refractive error seen in this study is similar to the result of a study conducted in Western Saudi Arabia among 3-10 years old children which reported a prevalence of 34.9% of uncorrected refractive error among this population (2). Also, this prevalence is comparable to what was reported in Imphal, Manipur India, where the prevalence of 29.14% refractive error among school children was also reported (8). These similarities may be explained by the fact that both studies adopted a similar working de nition for refractive error, that is:…”
Section: Discussionsupporting
confidence: 89%
“… 16 , 21 , 22 In accordance with a previous study, longer durations of reading, use of a computer, playing video games, and watching television were each defined as ≥2 hours per day. 23 Shorter duration of engaging in outdoor activity was defined as any outdoor daily visual activity performed for <1 hour. 11 Positive family history of RE was defined as a history of spectacle wear for RE in any family member.…”
Section: Methodsmentioning
confidence: 99%
“…Similar observation reported by more recent studies have demonstrated a positive correlation between the presence of myopia and prolonged work requiring near vision use. [25,26,27,28,29,30] Dixit R. et al did not find any significant association between screen usage and refractive error. [31] In this study it is observed that playing outdoor game is significantly negatively associated with refractive error.…”
Section: Discussionmentioning
confidence: 99%